FUNDAMENTAL FILSAFAT ILMU DALAM KONTRUKSI KURIKULUM MERDEKA BAGI MAHASISWA PAI PERSPEKTIF ABAD 21 - Aulia, Rahma; Prabowo, Tri Wahyudi Fajar; Putri, Aisyah Amalia; Faizin, Moh (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
The Covid-19 era has necessitated changes in Indonesia's education system to make it more contemporary and relevant. Education, being dynamic, must evolve with the times and adapt to societal conditions. In this context, the curriculum plays a pivotal role in constructing a more appropriate education system. This involves incorporating critical thinking, logical reasoning, and diverse perspectives. The Program for International Student Assessment (PISA) serves as a benchmark, while the philosophy of science acts as a critical analytical tool. The aim of this discussion is to integrate various elements, specifically the philosophy of science, an independent curriculum, and Islamic education (PAI) students. This research employs a descriptive qualitative approach, utilizing library research or literature review methods for data collection. The discussions and findings culminate in the development of an independent curriculum, conceptualized as the "educational change trilogy." This curriculum is then integrated with Islamic education in Indonesia. By combining problem identification, solution development, and result analysis, this study proposes a comprehensive framework for educational reform in Indonesia